2022
DOI: 10.1007/s00405-022-07432-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the lingual nerve for palate surgery: where is located and how to avoid it

Abstract: Purpose To describe the anatomic relationship of the lingual nerve with the lateral oropharyngeal structures. Methods An anatomic dissection of the lateral oropharyngeal wall was conducted in eight sides from four fresh-frozen cadaveric heads. Small titanium clips were placed along the lingual nerve and the most anterior and medial border of the medial pterygoid muscle. Radiological reconstructions were employed for optimal visualization; the coronal view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The PMR forms the anterior wall of the pterygomandibular space, an important cavity containing the inferior alveolar nerve, artery and vein, the lingual nerve, the nerve to mylohyoid, and the sphenomandibular ligament [ 20 , 21 ]. Medial to the prestyloid compartment, the PMR’s medial surface is covered by oral mucosa [ 1 , 9 ]. The lateral surface, however, is disconnected from the ramus of the mandible by a layer of buccal fat pad-derived adipose tissue [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The PMR forms the anterior wall of the pterygomandibular space, an important cavity containing the inferior alveolar nerve, artery and vein, the lingual nerve, the nerve to mylohyoid, and the sphenomandibular ligament [ 20 , 21 ]. Medial to the prestyloid compartment, the PMR’s medial surface is covered by oral mucosa [ 1 , 9 ]. The lateral surface, however, is disconnected from the ramus of the mandible by a layer of buccal fat pad-derived adipose tissue [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…While some deny its existence, others support it ( Figs. 2 , 3 ) [ 3 , 8 , 9 , 22 - 24 ]. After studying 50 hemiheads, Gaughran [ 25 ] concluded that the PMR was an anatomical artifact, citing the continuous nature of the bucinator and the SPC in all specimens.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations